Analisis Sistem Pendidikan Di Sekolah Indonesia Kuala Lumpur (SIKL) : Perspektif Guru - Setyani, Setyani; Zuliyana, Fina; Rofitrasari, Rofitrasari; Amelia, Nila; Ahsani, Eva Luthfi Fakhru (UNIB Press, 2021)
This study is to determine the education system in SIKL schools from the teacher's perspective, to determine the differences in the education system in SIKL and in Indonesia, to determine the barriers to education in SIKL, and to determine the role of teachers in the education system in SIKL. SIKL is an Indonesian school located in Kuala Lumpur. The uniqueness of SIKL is in feedback, progress, blue print and online. This study uses a qualitative research approach. The difference in the education system in SIKL and in Indonesia is one of them in the level of education. Barriers to education in SIKL are infrastructure, adsminitrative and documentary facilities. How to become a teacher or school principal in SIKL in a way. Must have extra patience. Due to limited infrastructure, excess working hours, the social environment is different from Indonesia, these are challenges that must be resolved by the teachers in SIKL. Obstacles in SIKL can be minimized by maximizing human resources and infrastructure.